Formulation and Antioxidant Test of Nano Facial Wash Bay Leaf (Syzygium polyanthum) Extract with Green Surfactant from Ketapang (Terminalia catappa L.) Seed Oil - Mochammad Chasani; Senny Widyaningsih; Undri Rastuti; Vita Nuraisyah Dwi Nugroho (ALCHEMY Jurnal Penelitian Kimia, 2025)
The increasing use of skin care products today has encouraged the development of facial washes that are safe for health, such as those incorporating natural active ingredients. Green surfactants from ketapang seed oil and bay leaf extract are natural ingredients for a facial wash. This study aims to formulate and test a nano facial wash using surfactants derived from ketapang seed oil and antioxidants from bay leaf extract. The molecular size of facial wash has been improved by applying nanoemulsion technology, resulting in nano facial wash. This particle size improvement enhances the efficacy of active ingredients in facial wash. Methyl ester sulfonate (MES) surfactant made from ketapang seed oil was used to increase the stability and effectiveness of cleaning products. The resulting product was tested for physical characteristics, stability, and antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. The facial wash formulation was carried out with variations in MES concentration (3, 5, and 7%) and bay leaf extract (2, 4, and 6%). The results showed that the facial wash with the best characteristics had a surfactant content of 7% and bay leaf extract of 2%. The antioxidant activity of facial wash with the best nano and non-nano characteristics is 41.97 ppm and 81.58 ppm, which are classified as strong antioxidant activity.